Epidemiology of asthma in 94 children with atopic dermatitis - Cantani, Arnaldo (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2016)
In this paper we present 94 children affected with atopic dermatitis (AD), aggravated by respiratory allergy, asthma and/or allergic rhinitis (AR). AD is a common disorder, frequently complicated by asthma-like symptoms, we debate either disorder and conclude that both AR and asthma can afflict most babies with AD, especially when both parents smoke. We confirm our previous statistics, according to which little children not fed breast milk may react to smallest doses of allergens.